2023
DOI: 10.1002/cncr.34699
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer‐measured physical activity and postmenopausal breast cancer incidence in the Women's Health Accelerometry Collaboration

Abstract: Background: Few studies have examined accelerometer-measured physical activity and incident breast cancer (BC). Thus, this study examined associations between accelerometer-measured vector magnitude counts per 15 seconds (VM/15s) and average daily minutes of light physical activity (LPA), moderate-to-vigorous PA (MVPA), and total PA (TPA) and BC risk among women in the Women's Health Accelerometry Collaboration (WHAC). Methods: The WHAC comprised 21,089 postmenopausal women (15,375 from the Women's Health Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…28,32 Our findings align with other studies using accelerometer data that found physical activity may play a role in the prevention of PA-related cancers among older women 33 and for incident breast cancer. 15,16 In addition to finding lower risk for 7 of the 13 PA-related cancers identified by Moore and colleagues, 17 we also observed a protective association between total PA and non-Hodgkin lymphoma and suggestive associations for melanoma and pancreatic cancers.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…28,32 Our findings align with other studies using accelerometer data that found physical activity may play a role in the prevention of PA-related cancers among older women 33 and for incident breast cancer. 15,16 In addition to finding lower risk for 7 of the 13 PA-related cancers identified by Moore and colleagues, 17 we also observed a protective association between total PA and non-Hodgkin lymphoma and suggestive associations for melanoma and pancreatic cancers.…”
Section: Discussionsupporting
confidence: 77%
“…Existing accelerometer-measured activity studies in cancer have primarily focused on cancer mortality and, 1014 to a limited extent, breast cancer risk. 15,16…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation